2013
DOI: 10.1186/1477-7525-11-9
|View full text |Cite
|
Sign up to set email alerts
|

Factors associated with health-related quality of life among Indian women in mining and agriculture

Abstract: BackgroundWomen facing social and economic disadvantage in stressed communities of developing countries are at greater risk due to health problems. This paper investigates the relationships between structural, health and psychosocial predictors among women in mining and agricultural communities. This paper is a report of a study of the predictors of the health-related quality of life among Indian women in mining and agricultural communities.MethodsA descriptive cross-sectional research design was used. The ins… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
15
0
4

Year Published

2013
2013
2016
2016

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 22 publications
(25 citation statements)
references
References 51 publications
6
15
0
4
Order By: Relevance
“…In a study among 145 Indian women living in mining areas, women reported a loss of negotiating power, and poor health and well-being. In a study among 145 women in a mining community women had less decision making and reproductive health choices [12]. Spouses rather than the women themselves made reproductive choices about avoiding conception (40%), spacing (39%), number of children (39.3%), use of contraceptives (35.8%) and permanent family planning (33.1%) compared to women in the mining community [11].…”
Section: Introductionmentioning
confidence: 99%
“…In a study among 145 Indian women living in mining areas, women reported a loss of negotiating power, and poor health and well-being. In a study among 145 women in a mining community women had less decision making and reproductive health choices [12]. Spouses rather than the women themselves made reproductive choices about avoiding conception (40%), spacing (39%), number of children (39.3%), use of contraceptives (35.8%) and permanent family planning (33.1%) compared to women in the mining community [11].…”
Section: Introductionmentioning
confidence: 99%
“…A menor média de resposta foi para vitalidade (69,26±16,13 pontos) e a maior para capacidade funcional (92,03±15,75 pontos). Destaca-se que, dentre as pesquisas consultadas, apenas duas enfocaram a relação entre QV e mineração (D'SOUZA; KARKADA; SOMAYAJI, 2013;GARCÍA et al, 2011). Um número maior de estudos tem contemplado a correlação entre QV e os DORTs (MEIRA-MASCARENHAS; ORNELLAS-PRADO; HENRIQUE-FERNANDES, 2012;SCHMIDT;DANTAS, 2012;ROCHA;FAGUNDES, 2011;GOMES et al, 2010;SOUZA et al, 2010b O maior desconforto muscular foi para a região lombar, seguida da dorsal.…”
Section: Resultsunclassified
“…23 Women's coping strategy was one of important factor that influenced health and had positive relation with good quality life. 24 One of coping strategy was Emotional focused coping. Emotional focused coping, such as self-acceptance, humor, adaptation, and positive thinking, had positive relation with women's mental health.…”
Section: Psychology Respondmentioning
confidence: 99%